Oxidation of Quercetin and Kaempferol Markedly Amplifies Their Antioxidant, Cytoprotective, and Anti-Inflammatory Properties - Hernán Speisky; María Fernanda Arias-Santé; Jocelyn Fuentes (MDPI AG, 2023)
The contention that flavonoids' oxidation would necessarily lead to a loss of their antioxidant properties was recently challenged by the demonstration that quercetin oxidation leads to the formation of 2-(3,4-dihydroxybenzoyl)-2,4,6-trihydroxy-3(2H)-benzofuranone (Que-BZF), a metabolite whose antioxidant potency was notably higher than that of its precursor. Here, we compared and expanded the former observation to that of the quercetin analogue kaempferol. Oxidation of kaempferol led to the formation of a mixture of metabolites that included the 2-(4-hydroxybenzoyl)-2,4,6-trihydroxy-3(2H)-benzofuranone (Kae-BZF). Following the chromatographic isolation of Kae-BZF from such a mixture, its antioxidant, mitochondria- and cell-protecting, and NF-kB-inhibiting effects were assessed, and compared with those of Que-BZF, in Caco-2 cells exposed to indomethacin as a source of ROS. The concentrations of Que-BZF (100 nm) and Kae-BZF (1 nm) needed to attain their maximal protection effects were 50- and 5000-fold lower than those of their respective precursors. The former differences in concentrations were also seen when the abilities of Que-BZF and Kae-BZF to inhibit the indomethacin-induced activation of NF-kB were compared. These data not only reveal that the oxidative conversion of quercetin and kaempferol into their respective 2-benzoyl-2-hydroxy-3(2H)-benzofuranones (BZF) results in a considerable amplification of their original antioxidant properties, but also that the in the case of kaempferol, such amplification is 100-fold greater than that of quercetin.